Synthesis and Characterization of Quaternary Ammonium Salts Containing Carbonyl Functionality - Salim, Norazlinaliza (2007)
This study is mainly focused on the synthesis of quaternary ammonium salts (QASs) derived from long-chain ketones as starting materials. The procedure used in this study is an extension of a new procedure for the preparation of iodinated acetone successfully developed in our lab and shown to be a generalized procedure for the preparation of iodinated ketones (Wong (2002), Badri (2000)), used to produce a class of quaternary amines containing a carbonyl functionality. Eight new QASs were produced; N-acetonyl-3-methylpyridinium iodide (17), N-acetonyl-4-methylpyridinium iodide (18), N-(2-oxoheptan-3-yl)pyridinium iodide (19), 2-methyl-N-(2-oxoheptan-3-yl)pyridinium iodide (20), N-2-oxoundecanylpyridinium iodide (21), 3-methyl-N-(2-oxoundeca-3-yl)pyridinium iodide (22), N-(2-oxododecyl)pyridinium iodide (23) and N-acetonyltrioctylammonium iodide (24). These compounds were characterized by FT-IR, 1H and 13C NMR and CHN elemental analysis. Single crystal x-ray analysis was used to solve the structures of 17 and 18. The crystal systems for both compounds were monoclinic. In the surface tension study, it was found that all of the QASs prepared lower the surface tension of water. The critical micelles concentration (CMC) value for the compound 24 (0.0339 mM) is the lowest of all the quaternary ammonium compounds prepared. Qualitative and quantitative antimicrobial assays showed that not all of the QASs prepared were active against bacteria and fungi tested. Only some of them were found to be active against the microorganisms. The compound 23 was strongly active (diameter>15 mm) against Salmonella choleraessuis and Bacillus subtilis wild type with 20 mm and 25 mm diameter inhibition zones, respectively. There are higher than the control, Streptomycin (17 mm and 15 mm respectively). The presence of long-chain ketones moderately increases the inhibiting effect against the selected microorganisms. The MIC value for the compound 23 against Salmonella choleraessuis is 12500 μg ml-1. The MIC value for the compound 23 (1560 μg ml-1) against Bacillus subtilis is higher than the control, Streptomycin (48.8 μg ml-1).